Trust and Terror Social Capital and the Use of Terrorism as a Tool of Resistance - Shamaileh, Ammar (Taylor & Francis, 2017)
Why do some individuals choose to protest political grievances via non-violent means, while others take up arms? What role does whom we trust play in how we collectively act? This book explores these questions by delving into the relationship between interpersonal trust and the nature of the political movements that individuals choose to join. Utilizing the examples of the Arab Spring uprisings in Egypt, Libya and Syria, a novel theoretical model that links the literature on social capital and interpersonal trust to violent collective action is developed and extended. Beyond simply bringing together two lines of literature, this theoretical model can serve as a prism from which the decision to join terrorist organizations or violent movements may be analyzed.